Patient reported outcomes measures in neurogenic bladder and bowel: A systematic review of the current literature. Issue 1 (18th October 2014) - Patel, Darshan P.; Elliott, Sean P.; Stoffel, John T.; Brant, William O.; Hotaling, James M.; Myers, Jeremy B.
Abstract : Aim: To describe existing bladder and bowel specific quality of life (QoL) measurement tools, QoL in patients with multiple sclerosis (MS), spinal cord injury (SCI), Parkinson's Disease (PD), stroke, or spina bifida (SB) affected by bladder or bowel dysfunction, and the impact of specific bladder and bowel management on QoL. Methods: We performed a systematic review in PubMed/Medline databases in accordance with the PRISMA statement for English publications between January 1, 2000 and January 1, 2014. Articles were first screened based on their abstract and select full‐text articles were then reviewed for eligibility. Articles with no QoL or PROM assessing urinary or bowel dysfunction were excluded. Risk of bias assessment included randomization, incomplete outcomes data, selective outcomes reporting, and other biases. All articles were graded using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system as per the Cochrane Handbook for Systematic Reviews of Interventions. Results: The most common QoL measurement tool for urinary and bowel dysfunction was the Medical Outcomes Study SF‐36. Twelve (24%) studies used only non‐validated QoL questionnaires. Only three urinary or bowel specific QoL measures were found: the Qualiveen questionnaire, the FICQoL, and the QoL‐BM. Several studies identified instances were clinical and patient‐reported outcomes were inconsistent particularly with indwelling urinary catheter usage and reconstructive surgery. Additionally, certain clinical outcomes surrogates commonly used as primary outcomes measures may not correlate with the patient reported outcomes (PRO). Conclusions: Current PRO measures (PROM) and QoL assessments are heterogeneous and several inconsistencies in clinical and PRO for various management options exist. Standardized PROM will help identify optimal bladder and bowel management for patients with neurologic conditions. Neurourol. Urodynam. 35:8–14, 2016 . © 2014 Wiley Periodicals, Inc.